Dependence of the fracture toughness on the sintering time of dense hydroxyapatite bioceramics - Tolouei, R.; Singh, R.; Sopyan, I.; Yong, T.C.; Amiriyan, M.; Dung, T.W. (International Conference on Frontier of Nanoscience and Technology (ICFNST 2011), 2011)
Fracture toughness dependence of sintered hydroxyapatite (HA) bioceramics on the sintering time was studied. The nanocrystalline and highly pure Hydroxyapatite powders produced by wet chemical precipitation method were used as starting material. After uniaxial and cold isostatic pressing, the green HA samples sintered at temperatures ranging from 1000 degrees C to 1300 degrees C with different sintering time. Dense compacts with grain sizes in the nanometer to micrometer range were processed. The average grain size of HA compact sintered at 1000 degrees C was around 500 nm. Grain size increased to 3 pm when the compacts were sintered at higher temperature. The average microhardness value of sintered HA decreased with an increased in grain size. Indentation fracture toughness for HA compacts of 700 nm grain size was 1.41 +/- 0.4 MPa.m(1/2) which is similar to fracture toughness of human cortical bone.